INTERVENTIONS DE LEADERSHIP CONSCIENT ET POSITIF : L'IMPACT SUR LES EXPÉRIENCES, LES CARACTÉRISTIQUES ET LES COMPORTEMENTS POSITIFS - Laurent GIRAUD; Soufyane FRIMOUSSE; Yves LE BIHAN (Revue de Gestion des Ressources Humaines, 2022)
The present paper investigates the effects of a positive and mindful leadership intervention on the positive experiences, traits, and behaviors of managers and their employees. Our research design is a quasi-experimentation with randomized pretests and posttests performed on a specific control group: in a French pharmaceutical company, a group of 36 managers attended a 10-day Positive Psychology Intervention (PPI) focusing on positive and mindful leadership. Data collected before (T1) and after (T2) the intervention shows that positive experiences and behaviors increased, while positive traits were reinforced among the participants - yet not among members of the control group. These observations were cross-checked with data collected at the employee level. More precisely, the results indicate that after the intervention (T2), managers felt more empathy, mindfulness, and consonance while experiencing less stress. Similarly, at T2, employees confirmed that their trained who took part to the intervention were more mindful and displayed more collective awareness. Moreover, these employees perceived that their managers sensitized to positive psychology and mindfulness demonstrated additional procedural fairness and additional organizational civic virtues. The theoretical, empirical, and managerial contributions of this study are also discussed.